Refractive index and optical absorption properties of the complexes of a cyclobutane containing thiazolyl hydrazone ligand - Yakuphanoğlu, Fahrettin; Cukurovali, A; Yilmaz, I (Elsevier, 2005)
The optical behavior of the complexes of 4-(1-methyl-1-mesitylcyclobutane-3-yl)-2-(2-hydroxy-5-methoxybenzylidenehydrazino) thiazole was investigated by optical reflectance and transmittance measurements. The optical band gaps were determined by optical absorption spectra. The optical band gaps, which turned out to depend significantly on the metal coordination were calculated by optical absorption method. Type of optical transition responsible for optical absorption was direct transitions. Urbach plots exhibit two different exponential regions with different slopes and Urbach energies are combined of two linear functions. The refractive index and extinction coefficient of the complexes were determined in the visible range as a function of wavelength. The differences in the optical constants were observed in the investigated wavelength ranges. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: optical absorption; refractive index; metal complex